Becoming first-generation. Issue 2 (24th January 2022) - Vega, Blanca Elizabeth
Abstract : Purpose: The purpose of this paper is to understand how I – and many other students – became first-generation college students (FGCSs) by exploring the rise and retraction of TRIO. Originally, TRIO was a set of three college access and retention programs created in the 1960s to address the needs of a population designated as academically and economically disadvantaged. The author uses the term "becoming" as a process of how a person is constructed socially, in this case, as a FGCS and faculty member. The author uses. social construction of targeted populations theory to explore my testimonio as a beneficiary of opportunity programs. Design/methodology/approach: To explore how FGCS experience policy changes affecting TRIO, I use my testimonio to build on the historical literature that covers 1968–2001. I begin my testimonio by first reviewing my background as a second generation Ecuadorian American. I then review how I encountered opportunity programs and why I continued to be a participant in these programs, specifically, TRIO. I end my testimonio by countering criticism of TRIO programs using research on and lived experiences with TRIO. Findings: During an era when TRIO budgets remain under constant attack, testimonios shed light on participants' experiences with policy changes. Specifically, I reveal how economic budget cuts create policy changes to terms such as "academically and economically disadvantaged" and shapes perceptions and knowledge about who are FGCS. Research limitations/implications: Research limitations include application of social construction of targeted group theory to one testimonio. Implications include more studies on how policy changes, specifically budget allocations could affect characterizations and images of targeted populations such as FGCS. Practical implications: Understanding the role of policy changes to TRIO program funding benefits students from misperceptions by educational administrators and other stakeholders. Originality/value: My testimonio also builds on work regarding the impacts of CARPS on FGCS like me. Most importantly, my testimonio contributes to the efforts necessary to ensure these programs continue to exist and succeed. I use my testimonio side by side with research literature on TRIO to become both the subject of inquiry and the inquirer, simultaneously a beneficiary and an informant of how these programs have influenced my persistence through the postsecondary education system and shaped my understanding of FGCS.